COBOL systems migration to SOA: Assessing antipatterns and complexity - Mateos Diaz, Cristian Maximiliano (2019)
SOA and Web Services allow users to easily expose business functions to build larger distributed systems. However, legacy systems - mostly in COBOL - are left aside unless applying a migration approach. The main approaches are direct and indirect migration. The former implies wrapping COBOL programs with a thin layer of a Web Service oriented language/platform. The latter needs reengineering COBOL functions to a modern language/ platform. In our previous work, we presented an intermediate approach based on direct migration where developed Web Services are later refactored to improve the quality of their interfaces. Refactorings mainly capture good practices inherent to indirect migration. For this, antipatterns for WSDL documents (common bad practices) are detected to prevent issues related to WSDLs understanding and discoverability. In this paper, we assess antipatterns of Web Services’ WSDL documents generated upon the three migration approaches. In addition, generated Web Services’ interfaces are measured in complexity to attend both comprehension and interoperability. We apply a metric suite (by Baski & Misra) to measure complexity on services interfaces - i.e., WSDL documents. Migrations of two real COBOL systems upon the three approaches were assessed on antipatterns evidences and the complexity level of the generated SOA frontiers - a total of 431 WSDL documents.